Islamic Character Education in the Era of Industry 5.0: Navigating Challenges and Embracing Opportunities - Adiyono Adiyono; Syamsun Ni’am; Ahmad Muhtadi Anshor (Al-Hayat: Journal of Islamic Education, 2024)
This research examines the challenges and opportunities of Islamic character education in the context of the digital world in the era of Industrial Revolution 5.0. This era has changed the landscape of Islamic character education, with digital technology increasingly penetrating everyday life. This research uses a mixed methods approach by combining qualitative and quantitative methods. A qualitative approach was used through interviews and observations. A quantitative approach was carried out through a survey with an online questionnaire. Data were analyzed using thematic analysis methods and descriptive statistics. The research results show several challenges in implementing Islamic character education in the digital world. These include a lack of public understanding of the character of Islam, unequal access to technology, and the potential for conflict between traditional values and the impact of digital technology. However, this research also identifies significant opportunities, such as greater access to Islamic character education resources via the Internet, innovative educational applications, and the possibility of global collaboration to develop Islamic character. In conclusion, Islamic character education in the digital world in the era of the Industrial Revolution 5.0 offers significant challenges but also great opportunities. The originality of these findings lies in a holistic understanding of the impact of the Industrial Revolution 5.0 on Islamic character and efforts to educate it.